Electroacupuncture attenuates LPS-induced depression-like behavior through kynurenine pathway - Xingying Wu; Rong Hu; Shuo Jiang; Zhong Di; Yi Chen; Mengting Shi; Bowen Chen; Kelin He; Kelin He; Kecheng Qian; Qin Guo; Ruijie Ma; et al. (Frontiers in Behavioral Neuroscience, 2023)
BackgroundA growing body of evidence suggests that inflammation and changes in glutamate neurotransmission are two pathophysiological mechanisms underlying depression. Electroacupuncture (EA) is a common therapeutic tool for the treatment of depression. However, the potential antidepressant mechanism of EA remains obscure. The change of the kynurenine pathway (KP) is the research priority of antidepressant mechanisms. This study will investigate the role of EA on lipopolysaccharide (LPS)-induced depression-like behavior and explore its possible mechanism of action.MethodsLipopolysaccharide was used to induce depression-like behavior, and EA was given at Hegu (L14) and Taichong (LR3) acupoints in C57BL/6J mice. Depression-like behaviors were measured by behavioral tests, including tail suspension test (TST), sucrose preference test (SPT), force swim test (FST), and open field test (OFT). The levels of inflammatory cytokines IL-1β, IL-6, and TNF-α, and KP enzyme IDO1 were measured by qPCR and enzyme-linked immunosorbent assay (ELISA), while high-performance liquid chromatography (HPLC) was performed to detect the content of prefrontal cortex and hippocampal as well as serum glutamate, tryptophan (TRP), kynurenic (KYN), and quinolinic acid (QA).ResultsThe results showed that (1) as evidenced by increased spontaneous locomotor activities, decreased immobility duration, and a stronger preference for sucrose in the sucrose preference test, EA reversed LPS-challenged depressive-like behavior. (2) EA at L14 and LR3 decreased the levels of inflammatory cytokines, inhibited IDO1, and regulated KP metabolisms, as well as lowered the concentration of glutamate. (3) EA may exert anti-depression effects by acting on the kynurenine pathway.ConclusionThis study evaluated the effects of EA on depression-like behaviors induced by lipopolysaccharide (LPS) and its regulation of inflammation and the glutamatergic system. Our results suggest that EA can ameliorate depression-like behaviors, lower the level of inflammation, and reduce the release of glutamate, possibly through the regulation of the kynurenine pathway in the brain.